Potential Of Nata De Legen In Improving Local Wellness Of Natural Resources And Human Resources In Dalegan Village, Gresik District - Asri, Mahanani Tri; Ducha, Nur; Ratnasari, Evie; Bashri, Ahmad (Universitas Tanjungpura, 2018)
Dalegan Village of Gresik District, East Java, is a large Legen / neera and Palmyra fruit producing village. During this time legen siwalan was sold in the form of natural drinks. The problem faced by partners at this time is this Palmyra fruit spoils relatively quick so it doesnâ€™t have high selling value. A technology is needed in the form fermentation to produce Nata de Legen using Acetobacter xylinum. Training method used were in form of lectures, demonstrations, discussions, direct practice, independent tasks, evaluation and marketing trials. The training was conducted in 3 groups consisting of 10 Local Welfare Organization (PKK) members and 5 Youth Organization members. The expected output target at the end of the program is that all participants succeeded in making the starter and Nata de Legen correctly. Participants also managed to whiten and soften raw Nata, which then made into end-products in the form of fruit-flavored Nata de Legen drinks (honeydew, strawberry, orange and cocopandan) and desserts in form of jelly and pudding packed in cup and bulk with the selling price calculated accordingly to Nata de Legen entrepreneurial training.Â